2022
DOI: 10.1080/0142159x.2022.2093704
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment: With all its limitations, why are we still measuring and teaching it? Lessons from a scoping review

Abstract: Self-assessment: with all its limitations, why are we still measuring and teaching it? Lessons from a scoping review. Intro: Self-Assessment (SA) is often assumed to be essential for learning, however this assumption has been extensively rebutted. Research shows SA has significant limitations, including its lack of correlation with competence. Method:We undertook a scoping review of SA in medical education (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021) and surprisingly discovered substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…Our finding of a differential impact of training on confidence versus demonstrable skills is consistent with a long-standing, substantial body of research examining the relationship between self-assessment and objective measures of learning [ 28 , 65 , 66 ]. The pattern of non-existent, weak, or even inverse relationships between the two has been shown for a variety of medical staff trainee and education learner groups [ 28 , 29 , 67 72 ].…”
Section: Resultssupporting
confidence: 87%
“…Our finding of a differential impact of training on confidence versus demonstrable skills is consistent with a long-standing, substantial body of research examining the relationship between self-assessment and objective measures of learning [ 28 , 65 , 66 ]. The pattern of non-existent, weak, or even inverse relationships between the two has been shown for a variety of medical staff trainee and education learner groups [ 28 , 29 , 67 72 ].…”
Section: Resultssupporting
confidence: 87%
“…Studies have demonstrated that selfassessment of knowledge and skill performance is often inadequate and lack correlation with competence. 19 In medical education, there is a dearth of evidence on how mastery of airway skills is attained, and life-long learning achieved. 20 We found a positive correlation between previous experience with FBI and performance, but volume of practice does not necessarily translate into level of expertise.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, physicians received no feedback between cases. Studies have demonstrated that self‐assessment of knowledge and skill performance is often inadequate and lack correlation with competence 19 …”
Section: Discussionmentioning
confidence: 99%
“…This is because self-assessment accuracy of a skill does not correlate with improved performance in that skill. 16 Instead, attention has moved to understanding the process of ISA as a strategy for learning, and how this can be supported. Changing patterns in self-assessment describe, but do not explain how and why medical students learn to balance, synthesise and reconcile available data to inform self-assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The focus in self-assessment research has shifted away from studies of accuracy. This is because self-assessment accuracy of a skill does not correlate with improved performance in that skill 16. Instead, attention has moved to understanding the process of ISA as a strategy for learning, and how this can be supported.…”
Section: Introductionmentioning
confidence: 99%